Ethnic differences in gender‐typical occupational orientations among adolescents in Germany - Wicht, Alexandra [Verfasser]; Siembab, Matthias [Verfasser] (My University, 2022)
„We illuminate the socio‐cultural embeddedness of adolescents to explain gender‐typical occupational orientations (GTOO) from an intersectional perspective. We investigate whether and why immigrant and native youths differ in their GTOO. These issues are of practical and political importance, as deviations from the norm of the autochthonous majority society can drive change in the gender segregation of the labor market on the one hand but can also lead to difficulties in accessing training and work on the other. We use cross‐sectional data on ninth‐graders from the German National Educational Panel Study, which allows us to analyze distinct dimensions of GTOO, i.e., expectations and aspirations. The results of step‐wise multilevel models show that (a) differences in GTOO between immigrant and native youths apply to certain countries of origin—particularly females from Turkey, the country with the strongest contrast to the German context in terms of gender‐related labor market characteristics, differ in their aspirations from native females—and (b) differences between immigrant and native German expectations shrink with immigrant generation and after controlling for aspirations. This indicates that assimilation processes involving socialization‐related adaptation to the host society play a greater role than an increase in information about its labor market.“ (authors’ abstract; BIBB-Doku)
Keywords: L 5 Beratung & Orientierung; P 1.5 Migranten; 370; Berufsorientierung; Berufswahl; Bildungsaspirationen; Geschlechtsspezifische Faktoren; Geschlechterverteilung; Migrationshintergrund; Ethnische Herkunft; ausländischer Jugendlicher; Nationales Bildungspanel